Financial Ratios and Corporate Performance: The Interaction of Liquidity, Solvency, and Profitability in Indonesian Mining Companies - Muhamad Jorgi Rahmat Andri Sumarlin; Miranda Hotmadia Tanjung (Publikasi Indonesia, 2025)
This study examines the impact of liquidity and solvency ratios on the financial performance of mining companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Amid global commodity price volatility and the implementation of downstream policies in Indonesia's mining sector, the management of financial structures is becoming increasingly critical. Liquidity is measured using cash ratios and quick ratios, while solvency is represented by debt-to-equity ratio (DER) and debt-to-asset ratio (DAR). Financial performance is assessed using profitability indicators such as Return on Assets (ROA) and Return on Equity (ROE) with company size, company age, and exchange rate as control variables. Panel data regression using the Random Effects Model (REM) revealed that DAR had a significant negative effect on ROA, while DER significantly and negatively affected ROE. In contrast, the liquidity ratio did not show a significant effect on profitability. These findings suggest that excessive debt can hinder profitability and that maintaining an optimal capital structure is essential for sustainable financial performance in Indonesia's capital-intensive mining industry. This study provides empirical insights for the formulation of financial strategies in resource-based sectors that are vulnerable to external shocks.